(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Pavement stress-strain analysis is an ideal tool for analytical modelling of pavement behaviour and thus, constitutes an integral part of pavement design and performance evaluation. It is the fundamental basis for the mechanistic design theory. Predicting pavement response by simplified procedure analysis by relying on equivalency factors using axle load spectrum which is obtained from Weigh-In-Motion (WIM) data is aimed for this study. The framework for computing the structural response of the standard axle group loads on a pavement structure by using a layered elastic computer program and calculation of pavement responses for axle load distribution for different axle groups and axle types by using the theoretical analysis. From the study, the summary of the obtained results are as follows: (1) axle load distribution was developed for the four considered axle configurations; (2) Single axle with single tyre has the greatest destructive impact followed by the tridem axle with dual tyres (TRDT) and next by TADT. The least destructive axle group type is the Single Axle with Dual tyre SADT.The predicted pavement response by theoretical analysis indicates that the critical tensile strains obtained results are all greater than the critical vertical strains. At the heaviest axle load, from 70KN, for both SAST and SADT; from 140KN for TADT; and from 210KN, the critical strains have the greatest magnitude by SAST and followed by SADT and next by TADT. The least critical tensile strain is from the TRDT.